Differential separation of albite from microcline by monovalent salts in HF medium - Demir, Cengiz; Gülgönül, İlhan; Bentli, İsmail; Çelik, Mehmet S. (Springer Science and Business Media LLC, 2003)
Na-feldspar (albite) and K-feldspar (microcline or orthoclase) are major feldspar minerals with identical crystal structures and physico-chemical properties. Flotation appears to be a unique method of separating these minerals. Fundamental studies on an amine/feldspar system in the presence of monovalent salts have shown that separation of these feldspar minerals by flotation is possible at certain a concentration of monovalent salts at natural pH. In this study, flotation separation in hydrofluoric acid (HF) medium in the presence of salt was found to occur at higher amine concentrations at natural pH. A general mechanism based on differences in the charge of albite and microcline is proposed to be responsible for creating a surface charge on albite and microcline onto which amine adsorbs.
Keywords: Microcline; Feldspar; Flotation; Hydrofluoric acid; Albite; Hydrofluoric Acid; Amine